Innovative organic nutrient management and land arrangements improve soil health and productivity of wheat (Triticum aestivum L.) in an organic farming system - Sharma, Adarsh; Sharma, S. K.; Vyas, Latika; Yadav, Sharvan Kumar; Pramanick, Biswajit; Siddartha Naik, B. S. Sai; Obročník, Oliver; Bárek, Viliam; Brestic, Marian; Gaber, Ahmed; Alshehri, Mohammed Ali; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2024)
Introduction: Excessive use of fertilizers, chemicals, and irrigation harms soil fertility, leading to reduced yields and degradation. Organic farming offers a promising solution. This study hypothesized that an appropriate land arrangement, combined with split applications of farmyard manure (FYM) and liquid organic fertilizer can enhance wheat productivity while also improving soil health. Methods: The experiment was arranged in a split-plot design, with three land arrangements/ sowing methods in the main plot and eight nutrient management approaches in the subplots. Results: Concerning different land arrangements, the furrow irrigated raised bed sowing (FIRB) method resulted in the maximum wheat yield (4.34 t ha -1 ) as compared towith flat row sowing and zero tillage sowing.ConcerningWith respect to nutrient management practices, it was found that 75%75% of the recommended dose of N (RDN) through the FYM aswas basal + 2525% % RDN with the 1 st irrigation + Jeevamrut application at 500 L ha -1 during sowing, and the 1 st irrigation + Panchagavya spraying at 5% during the booting stage resulted in the highest grain yield (4.47 t ha -1 ). Both the zero tillage and FIRB land arrangements resulted in better soil biological activities and microbial countcounts than thedid flat sowing. The results indicate that sowing wheat usingvia the FIRB method, with the recommended nitrogen dose applied through split applications of FYM along with liquid organic manures such as Jeevamrut and Panchagavya, can be an excellent option for organic wheat cultivation. This approach can enhance both yield and soil health. Conclusion: 75 %Seventy-five percent RDN through FYM as a basal + 2525% % RDN during the 1 st irrigation + Jeevamrut at 500 L ha -1 during sowing and the 1 st irrigation + spraying of Panchagavya at 55% % during the booting stage is effective for increasingeffectively increased the growth and yield of organic wheat. ConcerningWith respect to land arrangements, both FIRB and zero tillage sowing resulted in better growth, yield, and soil biological properties. The practical utility of thethis study is the optimization of split applicationapplications of FYM and land arrangementarrangements for organic wheat cultivation.